2022
DOI: 10.3390/math10081270
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Deep Neural Network with Fuzzy Wavelets and Integrating an Inline PSO to Predict Energy Consumption Patterns in Urban Buildings

Abstract: Energy has been one of the most important topics of political and social discussion in recent decades. A significant proportion of the country’s revenues is derived from energy resources, making it one of the most important and strategic macro policy and sustainable development areas. Energy demand modeling is one of the essential strategies for better managing the energy sector and developing appropriate policies to increase productivity. With the increasing global demand for energy, it is necessary to develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…For selecting the optimal BFTIs, Zhou et al [69] proposed a multiobjective function consisting of a BFTI's smallest occlusion and its largest facade texture area. Ahmadi et al [70] used deep neural networks with fuzzy wavelets to predict Iranian energy demand. Among the innovative studies presented by Zhou et al [71], one focuses on the design of airborne-oriented supercontinuum laser hyperspectral (SCLaHS) LiDARs with 50 bands but with a 20 nm spectral resolution and a 0.5-meter ground sampling distance (GSD).…”
Section: Wireless Communications and Mobile Computingmentioning
confidence: 99%
“…For selecting the optimal BFTIs, Zhou et al [69] proposed a multiobjective function consisting of a BFTI's smallest occlusion and its largest facade texture area. Ahmadi et al [70] used deep neural networks with fuzzy wavelets to predict Iranian energy demand. Among the innovative studies presented by Zhou et al [71], one focuses on the design of airborne-oriented supercontinuum laser hyperspectral (SCLaHS) LiDARs with 50 bands but with a 20 nm spectral resolution and a 0.5-meter ground sampling distance (GSD).…”
Section: Wireless Communications and Mobile Computingmentioning
confidence: 99%
“…Chen et al (2021) suggested using LSTM and clustering algorithms to predict human N6-methyladenosine (m6A) sites [11]. Ahmadi et al (2022) presented a novel model for energy forecasting that incorporates a deep convolutional neural network with fuzzy wavelets and a PSO method [12]. An expert system in [13] is considered for detecting brain tumors from MRI images.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are studies with the application of several multicriteria decision support methods, in individual or hybrid form, as well as proposals for specific models aimed at solving electrical energy problems. This reveals trends to use models with Machine Learning and Neural Networks, for example, to infer results on production, efficiency and consumption of electricity (Ahmad et al, 2021;Ahmadi et al, 2022;Buțurache & Stancu, 2022;Kwakkel & Pruyt, 2013;Rolnick et al, 2022;Vargas-Solar et al, 2022). In addition, there are proposals for models for analyzing problems using Fuzzy logic, a theory for the mathematical treatment of data imprecision (Al-Barakati et al, 2022;Ervural et al, 2018a, b;Panchal et al, 2022;Qi et al, 2020;Zhou et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%